OPTIMIZING FIQH EDUCATION WITH A LOCAL INSIGHT TO IMPROVE HIGHER ORDER THINKING SKILLS IN MADRASAH - Rohimah, Siti; Wiarsih, Nur; Faishol, Riza; Baharun, Hasan (PENDIDIKAN SAINS DAN TEKNOLOGI, 2024)
This research aims to analyze the optimization of local-oriented Islamic jurisprudence education to improve higher order thinking skills in Madrasas. This research uses a qualitative case study type approach. The research subjects consisted ofHead of Madrasah, Deputy Head of Madrasah, Subject Teachers and students. Data collection techniques use observation, interviews and documentation. Data analysis techniques use data reduction, data presentation, and drawing conclusions. The research results show that Optimizing local-oriented Islamic jurisprudence education has indicatorsto achieve it Higher order thinking skills in Madrasas include,integration of local context, interactive learning, collaborative problem solving and critical literacy development. By integrating the local context in fiqh learning, students can more easily understand the material and are able to develop analytical, evaluation skills and create solutions to related problems. Implementation of locally based learning also increases active student participation and makes learning more meaningful. Thus, this research provides important implications for curriculum development and teaching strategies at Madrasah Aliyah, especially in order to increase students' HOTS through approaches that are relevant to their surrounding environment.